A Development of Web Application Package to Size a Grid Connected Photovoltaic System - Eusud, Ahmad Wafi Taqiuddin; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2022)
This project focuses on the development of a Web Application Package for Sizing a Grid-Connected Photovoltaic (PV) System. The Web Application Package is designed to have the capability to size the load consumption and determine the usage of every component for the grid-connected PV system, costing, and total payback period. System sizing is vital to ensure all the equipment that is used not producing extra energy needed which is related to the cost and total payback period. This Web Application Package can show all the procedures system sizing from load consumption until the total payback period of the single-story terrace house. The Web Application Package is created by using the Google Sites with the Integration of Calconic. The generated result from the Web Application Package application needs to correspond with the manual calculation to ensure the process of sizing the grid-connected PV system can be used for this project. Hence, it is important to do the correct sizing because the total payback period depends on the total monthly savings and the total cost of the PV system installation